Preparation of fluorescent carbon dots and application of fluorescent carbon dots in quantitative detection of curcumin based on fluorescence half-peak width change

By preparing doped carbon dots and using the half-maximum width change in fluorescence spectrum for quantitative detection of curcumin, the existing detection methods are solved, with high cost, large error and cumbersome pre-processing problems, and convenient, fast and cheap low-concentration detection is achieved.

CN119391410APending Publication Date: 2025-02-07GUANGXI UNIV FOR NATITIES
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411510089.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-28
Publication Date
2025-02-07

AI Technical Summary

Technical Problem

The existing methods for detecting curcumin content are costly, the fluorescence analysis method has obvious errors in detection and analysis indexes and the pretreatment process are cumbersome, making it difficult to achieve convenient, fast and inexpensive quantitative analysis.

Method used

The preparation method of doped carbon dots is adopted. By adding phosphorus salt to the carbon source and hydrothermal reaction with organic matter, a fluorescent carbon dot solution is prepared, and refined through filter membrane, centrifugation and dialysis steps to obtain fluorescence spectroscopy. Half-maximum width change quantitatively detects the doped carbon dots of curcumin.

Benefits of technology

The low-concentration detection of curcumin is realized, which reduces detection costs, reduces analysis indicator errors, simplifies the pre-processing process, and improves the accuracy and sensitivity of detection.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119391410A_ABST
    Figure CN119391410A_ABST
Patent Text Reader

Abstract

The preparation method comprises the following steps: adding a phosphor salt and urea into a carbon source, uniformly stirring, dissolving in water, carrying out a hydrothermal reaction at 180-200 DEG C, carrying out a series of purification operations such as suction filtration, high-speed centrifugation and dialysis, and obtaining the fluorescent carbon dots. Completely evaporating the solvent to dryness, replacing the solvent with equivalent absolute ethyl alcohol, fully dissolving by ultrasound, and filtering by using an organic filter head; the method solves the problems that the existing curcumin content detection cost is relatively high, the detection and analysis index error of a fluorescence analysis method is obvious, and the pretreatment process is relatively tedious. According to the method, after the curcumin and the fluorescent carbon dots have a synergistic effect, the characteristic half-peak width of a fluorescence emission spectrum of the coexisting solution, namely the light color purity in the coexisting solution, is regularly changed, and the content of the curcumin which promotes the change of the light color composition of the coexisting solution is measured according to the numerical value change condition of the half-peak width; and a curcumin quantitative analysis technology taking the high-performance fluorescent carbon dots as a detection medium is realized.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a doped carbon dot, and in particular to the preparation of a fluorescent carbon dot and the application of the fluorescent half-peak width change-based quantitative detection of curcumin. Background Art

[0002] Natural curcumin (Cur) is mainly found in the rhizomes of plants in the Zingiberaceae and Araceae families. It has excellent dissociation of diketone pigments and is usually used as a colorant. Trace amounts of curcumin ingested by the human body can play an antioxidant, prevent Alzheimer's disease and anti-inflammatory role. At present, curcumin has become a legal food additive in my country, and the pharmacopoeia law has clear requirements for the daily intake of the human body. Therefore, the development of a convenient, accurate and low-cost detection method to evaluate the curcumin content in food and medicine has become a key topic in the detection field.

[0003] The existing methods for determining the content of curcumin in food and medicine mainly include: spectrophotometry, fluorescence, liquid chromatography and electrochemical method. Among them, spectrophotometry and fluorescence are based on the characteristics of curcumin's fluorescence, and the fluorescence intensity is used as the analytical index for testing. However, due to the weak fluorescence of curcumin and the dark color of the solution, the fluorescence intensity analysis is more interfering and the error is obvious. At the same time, this method requires extremely high accuracy of the detection instrument, so the detection limit cannot reach a low concentration; and the fluorescence method usually uses detection media such as fluorescent carbon dots, etc., and the synergistic effect of the two produces changes in fluorescence properties to analyze the curcumin content, but this analysis index is affected by many factors. After ten seconds, the fluorescence intensity will change with a large error. The presence of interference, impurity and uneven dispersion of the solution will distort the fluorescence intensity. The fluorescence interference item must be strictly eliminated before the content and concentration can be determined. Liquid chromatography and electrochemical analysis are currently the most accurate methods for detecting curcumin concentration. However, the detection is often difficult because the mobile phase has difficulty separating higher concentrations and multiple detection interferences, or because of the difficulty in ensuring detection reliability, resulting in long detection times, difficult operating techniques, and expensive instrument maintenance costs. These problems are not conducive to convenient, rapid, and inexpensive quantitative analysis of curcumin content in food and medicine.

[0004] The existing quantitative detection technology of curcumin uses its fluorescence for determination. The technical means of fluorescence spectrophotometry and fluorescence method with the introduction of detection medium probes are as follows. The technical point of curcumin fluorescence spectrophotometry is to use the light intensity difference brought by a series of concentration gradients to achieve quantitative analysis. The existing literature 1 (Yan Jianwei, Bao Weiwen, Liang Bingqi, et al. Determination of curcumin in turmeric preparations by fluorescence spectrophotometry [J]. Chinese Modern Applied Pharmacy, 1998, (02): 44-45. DOI: 10.13748 / j.cnki.issn1007-7693.1998.02.029) can quickly and conveniently determine the concentration of pure curcumin, but the analysis index is fluorescence intensity, which is affected by precision density and human operation, and the data is highly volatile, so the data reliability needs to be improved; Literature 2 (He Mengyao, Jiang Xiuming, Li Junli, et al. Detection of curcumin in food based on hydrophobic carbon dot fluorescence resonance energy transfer system [J]. Henan University of Technology (Natural Science Edition), 2023, 44(06): 98-104.DOI: 10.16433 / j.1673-2383.2023.06.013) The detection probe fluorescent carbon dots were introduced. Fluorescent carbon dots were prepared from natural product linseed oil and used as the detection medium. The energy transfer between the dual fluorescent substances was carried out through the synergistic effect between curcumin and carbon dots. The light intensity between the dual-substance fluorescence system changed regularly to achieve quantitative analysis. Compared with the emerging carbon dot materials, the fluorescence of natural curcumin is weak. This method transfers the analysis index to the fluorescence intensity of the medium carbon dots, greatly improves the detection limit, and significantly reduces the error. At the same time, this method is simple to operate and has a low detection cost. However, the analysis index fluorescence intensity is affected by the differences in instrument accuracy and model stability, and the error caused by data fluctuation is still very obvious. Therefore, the existing detection of curcumin content is due to the weak fluorescence of the monomer, the error rate of the analysis index is high, the detection limit is high, and it is seriously interfered by other substances. Summary of the invention

[0005] The purpose of the present invention is to provide a preparation of fluorescent carbon dots and the application of quantitative detection of curcumin based on the change of fluorescence half-peak width, which solves the problems of high cost of existing detection of curcumin content, obvious error of fluorescence analysis method in detection and analysis index, and cumbersome pretreatment process. The method of the present invention abandons fluorescence intensity as a detection index, takes half-peak width as an analysis index, and realizes low-concentration detection of curcumin.

[0006] In order to achieve the above object, the present invention provides a method for preparing doped carbon dots for quantitatively detecting curcumin based on the change of half-peak width of carbon dot fluorescence spectrum, the method comprising:

[0007] (1) adding a phosphate salt and an organic substance containing only nitrogen-doped elements to a carbon source, stirring the mixture to uniformly dissolve in water, and performing a hydrothermal reaction at 180° C. to 200° C. to obtain a fluorescent carbon dot solution;

[0008] The carbon source is any one of glucose, starch, maltose, sucrose and lactose;

[0009] (2) The obtained fluorescent carbon dot solution is filtered with an aqueous filter membrane, and the supernatant is obtained by centrifugation. The supernatant is dialyzed with a dialysis bag in pure water under magnetic stirring. The liquid inside the dialysis bag is aqueous doped blue fluorescent carbon dots, which is recorded as aqueous N,P-CDs solution;

[0010] (3) The aqueous N,P-CDs solution was completely evaporated, anhydrous ethanol was added and fully dissolved again by ultrasound, and then filtered using an organic filter to obtain an alcohol-soluble N,P-CDs solution.

[0011] Preferably, in step (1), the phosphate salt is potassium dihydrogen phosphate, and the organic matter containing only nitrogen-doped elements is urea.

[0012] Preferably, in step (1), the molar ratio of the carbon source, the phosphorus salt and the organic matter containing only nitrogen-doped elements is (2-4):10:60.

[0013] Preferably, in step (2), the pore size of the water filter membrane is 0.45 μm; the centrifugal speed is 10000 r / min and the time is 10 min.

[0014] Preferably, in step (2), the molecular weight cutoff of the dialysis bag is 1000Da, the dialysis time is 16 to 48 hours, and the water is changed every 8 hours. The dialysis bag is used to remove the salt substances that do not participate in the reaction in the reaction system by retaining the large and removing the small. The dialysis bag of 100Da cannot remove the salt substances with a relative molecular mass of 300-500, so only 1000Da can be selected.

[0015] Preferably, in step (3), the pore size of the organic filter head is 0.22 μm.

[0016] The present invention provides a doped carbon dot for quantitatively detecting curcumin based on the fluorescence spectrum characteristics of the carbon dot, which is prepared by the preparation method as described.

[0017] Preferably, the doped carbon dots emit pure blue fluorescence at an excitation wavelength of 350 nm, with a light quantum yield of 41.86% and a fluorescence lifetime of 10.48 μs.

[0018] The present invention provides an application of the doped carbon dots described above in detecting the content of fluorescent organic matter, the application comprising:

[0019] As described above, the doped carbon dots are used as the detection medium, and the half-peak width of the fluorescence spectrum is changed by photophysical regulation to achieve quantitative analysis of the fluorescent organic matter to be tested.

[0020] Preferably, the application comprises detecting the content of curcumin: the curcumin and the doped carbon dots as described above are subjected to several bonding forces, so that the molecules are stacked super-closely, which triggers the size effect of the carbon dots, resulting in the phenomenon of spectral polychromatic emission, thereby affecting the half-peak width of the spectrum, and the curcumin content is analyzed by observing the half-peak width of the spectrum;

[0021] More preferably, the application comprises: setting the excitation wavelength of the fluorescence spectrophotometer to 350nm and the excitation voltage to 700V, adding the curcumin standard solution to the test solution containing the doped carbon dots as described above and mixing them evenly, recording the change of the half-peak width of the fluorescence emission spectrum, making a standard curve of the relationship between the curcumin content and the half-peak width, and calculating the curcumin content by substituting the half-peak width of the spectrum of the synergistic effect of the test sample and the carbon dots into the linear equation.

[0022] The preparation of fluorescent carbon dots and the application of quantitative detection of curcumin based on the change of fluorescence half-peak width of the present invention solve the problems of high cost of detecting curcumin content, obvious error of fluorescence analysis index detection and analysis method, and complicated pretreatment process, and have the following advantages:

[0023] 1. The fluorescent carbon dots prepared by the present invention have a main light color of blue fluorescence under short-wave excitation wavelength. Urea is used as a passivating agent to greatly improve the surface passivation degree of the fluorescent carbon dots, which leads to more surface defects and thus a higher ratio of electrons in the edge excited state of the carbon dots, thereby greatly increasing the fluorescence intensity. Potassium dihydrogen phosphate is used as a P-doped reagent, which works synergistically with the N element, which is beneficial to the ISC process of fluorescence emission. At the same time, with the carbon skeleton as the core, the N and P elements form a covalently cross-linked framework structure, which greatly suppresses the non-radiative transition, making the light intensity decay rate with time lower and the lifespan longer. Most of the carbon particles that fail to photoluminesce are removed during the fine purification process, and the solvent is changed to anhydrous ethanol to make the fluorescent carbon dots more dispersible in the liquid, avoiding the light intensity instability caused by regional deviations due to uneven distribution during the test process. At the same time, the solvent fits the solubility relationship of the detected object, so that the detection medium is fully in contact with curcumin, eliminating the interference of salt substances on the fluorescence spectrum, and greatly improving the detection accuracy. The detection method of the present invention utilizes the synergistic effect of curcumin and fluorescent carbon dots to cause the stacking of conjugated π domain sizes of the fluorescent centers of the carbon dots to cause obvious changes in the light color composition in the coexisting liquid, and measures the light color purity of the coexisting liquid by the change in half-peak width, thereby analyzing the curcumin content.

[0024] 2. Compared with the existing fluorescent carbon dot preparation technology, the present invention uses fluorescent carbon dots as the detection medium material, and further improves the fluorescence performance of carbon dots by doping. The greatly improved performance mainly includes light intensity, fluorescence lifetime, light intensity decay rate and quantum yield. At the same time, the solubility of the detected object is taken as the direction in the fine purification process. In the process of changing the solvent from water to ethanol, most of the carbon dots with poor thermal stability are removed, and finally dissolved in anhydrous ethanol for better dispersibility. The detected object curcumin has excellent alcohol solubility and poor water solubility. Most of the interfering salts are difficult to dissolve in anhydrous ethanol, which provides stable physical and chemical conditions for detection to ensure the accuracy of the detection results.

[0025] 3. Compared with the traditional fluorescence method for detecting curcumin, the detection method of the present invention regulates the conjugated π domain size of the fluorescence center of the detection medium fluorescence carbon dot with curcumin, realizes the phenomenon of spectral polychromatic emission and then affects the change of spectral characteristic half-peak width, by observing the half-peak width of the spectrum (observing the half-peak width of the spectrum is the light color composition, the data retest stability is high, only the light color composition in the solution is analyzed, and it is not affected by the large floating of light intensity) the curcumin content can be analyzed, and then the curcumin content and concentration in the sample to be tested are calculated by the standard curve. Because its trace amount of curcumin can have an impact on the carbon dot light color composition, and the reaction is sensitive, so the detection limit of the method of the present invention to the detection of curcumin content is extremely low. Therefore, the assay method of the present invention is novel, the anti-background interference power is strong, the analysis index error is small, and the detection limit is extremely low. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 This is a particle size distribution diagram of carbon dots prepared in Example 1 of the present invention and after interaction with curcumin.

[0027] Figure 2 This is a laser confocal microscope bright field / dark field scanning image after the carbon dots are prepared in Example 1 of the present invention and interact with curcumin.

[0028] Figure 3 Actual pictures of fluorescence excitation / emission of carbon dots prepared in Example 1 and Comparative Example 1 of the present invention.

[0029] Figure 4 The fluorescence emission spectra of the carbon dots prepared in Example 1 and Comparative Example 1 of the present invention are obtained by fluorescence spectrophotometry.

[0030] Figure 5 This is the scanning excitation / emission spectrum of carbon dots and curcumin prepared in Example 1 of the present invention.

[0031] Figure 6 The scanning electron microscope images of the carbon dots prepared in Example 1 of the present invention and the carbon dots prepared in the comparative example after co-acting with curcumin are shown.

[0032] Figure 7 EDS spectra of carbon dots prepared in Example 1 and Comparative Example 1 of the present invention.

[0033] Figure 8 The infrared spectra of carbon dots prepared in Example 1 and Comparative Example 1 of the present invention are shown.

[0034] Fig. 9 The Raman spectra of carbon dots prepared in Example 1 and Comparative Example 1 of the present invention are shown.

[0035] Fig.10 This is a graph showing the photon yield of carbon dots prepared in Example 1 and Comparative Example 1 of the present invention.

[0036] Fig.11 This is a graph showing the steady-state fluorescence lifetime results of carbon dots prepared in Example 1 of the present invention and Comparative Example 1.

[0037] Fig.12 The XPS peak diagrams of each element of the carbon dots prepared in Example 1 and Comparative Example 1 of the present invention are shown.

[0038] Fig.13 This is a graph showing the relationship between light intensity and pH stability, thermal stability and fluorescence decay rate of carbon dots prepared in Example 1 of the present invention.

[0039] Fig.14 This is a diagram showing the effect of quantitatively detecting curcumin using fluorescence spectral characteristics in the present invention.

[0040] Fig.15 A content-half peak width standard curve for quantitative detection of curcumin by carbon dots was prepared in Example 1 of the present invention.

[0041] Fig.16 The standard curves are obtained by different methods for determining curcumin in Comparative Examples 3 and 4 of the present invention. DETAILED DESCRIPTION

[0042] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0043] Example 1

[0044] A method for preparing lactose-doped blue fluorescent carbon dots, the method comprising:

[0045] (1) Using 0.001 mol of natural product lactose as raw material, 0.69 g of potassium dihydrogen phosphate and 0.42 g of urea were added as doping reagents to improve the performance of fluorescent carbon dots, and the mixture was fully stirred and evenly dissolved in 50 mL of pure water. The mixture was then transferred into a 100 mL polytetrafluoroethylene reactor and placed in a high-temperature drying oven at 180°C for 10 h for hydrothermal reaction. The reaction was then cooled naturally to obtain a fluorescent carbon dot solution. The molar ratio of potassium dihydrogen phosphate to urea was 1:6.

[0046] (2) The obtained fluorescent carbon dot solution was filtered through a 0.45 μm aqueous filter membrane to remove large particle impurities, and then centrifuged at 10,000 r / min for 10 min to obtain the supernatant. The supernatant was then dialyzed using a dialysis bag with a molecular weight cutoff of 1,000 Da in pure water under magnetic stirring for 16 to 48 h, with the water replaced every 8 h. The liquid inside the dialysis bag was aqueous lactose-doped blue fluorescent carbon dots (N, P-CDs), i.e., an aqueous N, P-CDs solution.

[0047] (3) Considering the physical properties of carbon dots and the solubility of the test object, the aqueous solution was replaced with anhydrous ethanol. 20 mL of the aqueous N,P-CDs solution was completely evaporated, and then 20 mL of anhydrous ethanol was added to fully dissolve it again by ultrasound. The carbon dot polymer particles with weak thermal stability were filtered out using a 0.22 μm organic filter. The remaining fluorescent carbon dots with excellent alcohol solubility were evenly distributed in anhydrous ethanol to obtain an alcohol-soluble N,P-CDs solution.

[0048] A method for quantitatively detecting the content of curcumin using the lactose-doped blue fluorescent carbon dots (N, P-CDs) based on the size effect of fluorescent carbon dots, the method comprising:

[0049] (1) Dilute the alcohol-soluble N,P-CDs solution 20 times to obtain a detection medium carbon dot solution for later use. Prepare 1×10 - 5 mol / L curcumin ethanol standard solution. During the detection process, a quartz cuvette was used to take 2mL of the detection medium carbon dot solution as the detection zero point mother solution to be tested.

[0050] (2) The fluorescence spectrophotometer was set at an excitation wavelength of 350 nm and an excitation voltage of 700 V. 20 μL of the curcumin ethanol standard solution was added to the zero-point mother solution to be tested 10 times and mixed thoroughly. The change in the half-peak width of the fluorescence emission spectrum was recorded to make a standard curve of curcumin content-half-peak width.

[0051] Comparative Example 1

[0052] A method for preparing fluorescent carbon dots with the same carbon source is basically the same as that in Example 1, except that:

[0053] In step (1), carbon dots with the same carbon source but different doping elements are prepared: non-doped type (CDs), N-doped type (N-CDs), and P-doped type (P-CDs).

[0054] The method for quantitatively detecting the curcumin content based on the size effect of the fluorescent carbon dots using the same carbon source prepared as above is the same as that in Example 1.

[0055] Comparative Example 2

[0056] A method for preparing N, P doped fluorescent carbon dots is basically the same as that in Example 1, except that:

[0057] In step (1), different carbon sources such as glucose, starch, sucrose, maltose, chitosan or bagasse powder are used.

[0058] The method for quantitatively detecting the curcumin content based on the size effect of the fluorescent carbon dots using the N, P-doped fluorescent carbon dots prepared above is the same as that in Example 1.

[0059] Comparative Example 3

[0060] A method for quantitatively detecting curcumin using fluorescence spectroscopy, the method comprising:

[0061] Referring to the method used in the existing quantitative detection method of curcumin (Yan Jianwei, Bao Weiwen, Liang Bingqi, et al. Determination of curcumin in turmeric preparations by fluorescence spectrophotometry [J]. Chinese Modern Applied Pharmacy, 1998, (02): 44-45. DOI: 10.13748 / j.cnki.issn1007-7693.1998.02.029), tetrahydrofuran was used as solvent to prepare 1×10 - 4 mol / L-10×10 -4 The curcumin test solution with a concentration gradient of mol / L was prepared by using a F-4600 fluorescence spectrophotometer from Hitachi, Japan, with an excitation wavelength of 442 nm to record the fluorescence intensity at 475 nm of the spectrum. The relationship between the fluorescence intensity and concentration of curcumin was determined by the fluorescence property of curcumin, and the content and concentration of curcumin were analyzed. The detection effect was compared with the curcumin detection method in Example 1.

[0062] Comparative Example 4

[0063] A method for quantitatively detecting curcumin based on the fluorescence resonance energy transfer principle of the prior art, the method (in order to compare the suitability of the materials and the advantages and disadvantages of the method effect in Example 1) comprising:

[0064] Based on the detection method of existing research results (He Mengyao, Jiang Xiuming, Li Junli, et al. Detection of curcumin in food based on hydrophobic carbon dot fluorescence resonance energy transfer system [J]. Journal of Henan University of Technology (Natural Science Edition), 2023, 44 (06): 98-104. DOI: 10.16433 / j.1673-2383.2023.06.013), carbon dots and curcumin are used as energy donors and acceptors respectively, and fluorescence resonance energy transfer is realized between the two. A series of curcumin test solutions with the same concentration gradient as Example 1 and alcohol-soluble N, P-CDs solutions are prepared to measure the fluorescence intensity under the condition of an excitation wavelength of 350nm, and the ratio of the fluorescence intensity I and I0 (carbon dot blank solution) at an emission wavelength of 425nm is recorded. The relationship between lg (I0 / I) and the curcumin concentration is obtained, and the quantitative analysis of curcumin can be realized. The advantages and disadvantages of the detection effect of this comparative example are compared with those of Example 1.

[0065] Experimental Example 1 Structural Performance Characterization

[0066] 1. Preparation of carbon dots in Example 1 and Comparative Example 1

[0067] The carbon dots prepared in Example 1 were measured using a Nicomp 380Z3000 nanometer particle size and potential analyzer. 1 mL of the carbon dot test solution in Example 1 and the non-doped carbon dot solution in Comparative Example 1 were taken, and 1 mL of 1×10 -5 mol / L curcumin ethanol standard solution, and then 20 μL of curcumin standard solution was added into the carbon dot test solution to measure the coexistence item particle size.

[0068] like Figure 1 As shown, the particle size distribution diagram of carbon dots prepared in Example 1 of the present invention and after the interaction with curcumin, wherein (A) is the particle size distribution diagram of carbon dots N, P-CDs in Example 1; (B) is the particle size distribution diagram of carbon dots CDs without any doping of lactose in Comparative Example 1; (C) is the particle size distribution diagram of curcumin alcohol solution; (D) is the particle size distribution diagram of carbon dots N, P-CDs after the interaction with curcumin. Figure 1It is known that the carbon dot N, P-CDs prepared in Example 1 is dispersed in an ethanol solution with an average particle size of 169.7 nm, while the lactose-based carbon dot CDs material prepared in Comparative Example 1 without any doping has an uneven particle size distribution and a larger particle size, which may be caused by the different degrees of carbonization caused by the doping reagent and the chemical bonds between the individual carbon dots. The force generated by the strong force causes them to agglomerate; the average particle size of the pure solid curcumin dissolved in the ethanol solution is 401.8 nm, and then 2 mL of the carbon dot test solution is taken and 20 μL of curcumin is added to make them fully contact, and then the particle size under the coexistence state is measured. From the results, it can be found that there are two obvious peaks in different particle size sections, the average particle size of peak 1 is 716.3 nm, and the average particle size of peak 2 is 158.7 nm. Obviously, the addition of curcumin makes it bonded and agglomerated with the carbon dots, which provides one of the necessary conditions for the ultra-close fitting of the two to form a luminescent domain conjugated π domain size stacked fluorescent multicolor emission.

[0069] In order to facilitate the observation of the fluorescence of the carbon dots prepared in Example 1, a non-fluorescent substance, sodium alginate, was introduced as a carrier to adsorb the prepared carbon dots to observe the luminescent group domain.

[0070] like Figure 2 As shown, the laser confocal microscope bright field / dark field scanning images of carbon dots prepared in Example 1 of the present invention and after the interaction with curcumin, wherein (A), (B) and (C) are bright field scanning images of the three, respectively, and (a), (b) and (c) are dark field fluorescence excitation images corresponding to (A), (B) and (C), respectively. Figure 2 From (a) and (A), it can be observed that the carbon dot carrier emits blue fluorescence after being given an excitation wavelength, so the carbon nanomaterial prepared by the present invention has fluorescence; Figure 2 From (b) and (B), we can see that curcumin also has fluorescence, but the light intensity is weaker. Figure 2 It can be seen from (c) and (C) that the two still have fluorescence when they coexist, and carbon dot materials can be observed to have particles with obvious fluorescence emission without using a carrier.

[0071] like Figure 3 As shown, the fluorescence excitation / emission real scene of carbon dots prepared in Example 1 of the present invention and Comparative Example 1. Figure 3 It is obvious that compared with the carbon dots in Example 1, the fluorescent carbon dot material prepared in Comparative Example 1 without any doping of carbon source has weaker fluorescence. After adding the passivating agent urea to dope with N, the light intensity is significantly enhanced. After adding dipotassium hydrogen phosphate to dope with P, it can be clearly found that the fluorescent light color of the carbon dots covers the visible light of the ultraviolet flashlight, and the excitation light energy conversion efficiency is higher than that of the undoped material.

[0072] like Figure 4 As shown, the fluorescence emission spectra of carbon dots prepared in Example 1 and Comparative Example 1 of the present invention are shown in the fluorescence spectrophotometer. Figure 4It can be seen that compared with the carbon dots in Example 1, the light intensity of the carbon dots in Example 1 that have not been doped and modified is weaker, and the higher instrument excitation energy indicates that the excitation energy conversion efficiency is low. After modification by N doping, the light intensity is greatly improved, and after modification by P doping, the instrument excitation energy peak is significantly reduced, and the carbon dot light energy conversion efficiency is improved.

[0073] like Figure 5 As shown in the figure, the scanning excitation / emission spectra of carbon dots and curcumin prepared in Example 1 of the present invention, wherein (A) is scanning excitation and (B) is scanning emission. Figure 5 It can be seen that the excitation wavelength of carbon dots is relatively wide, and the fluorescence effect produced by the excitation wavelength of 220-450nm is the best; the excitation wavelength of curcumin that can produce fluorescence is localized, and the fluorescence effect produced by the excitation wavelength near 300nm and 450nm is the best. From the fluorescence spectra of the two, the strongest fluorescence produced by carbon dots is near 450nm, and the strongest fluorescence emission of curcumin is at 570nm. The excitation wavelength of fluorescent carbon dots is very wide and the fluorescence intensity is higher than that of curcumin. Therefore, analyzing the curcumin intensity index alone may cause large data fluctuations and harsh detection conditions.

[0074] like Figure 6 As shown, the scanning electron micrographs of carbon dots prepared in Example 1 of the present invention and after co-action with curcumin, and carbon dots prepared in the comparative example, wherein (A) is non-doped carbon dots (CDs); (B) is carbon dots prepared by adding urea as a passivating agent (N-CDs); (C) is nitrogen and phosphorus co-doped carbon dots (N, P-CDs); (D) is a scanning electron micrograph of solid powder after N, P-CDs reacted with curcumin. Figure 6 It can be observed that the carbon dots prepared without doping are relatively rough and stacked in flakes, while the carbon dots powder prepared after doping is relatively fine and uniform. The carbonization degree of the modified nano-scale carbon material is higher, and it is easier to prepare small molecule nano-scale materials. After the carbon dots and curcumin act together, it can be found that the morphology has changed significantly. It is not the monomer morphology of the two, but the state of the two coated and separate particles. Therefore, there is a short enough contact distance between the two surfaces to match the stacking of the luminescent domain.

[0075] like Figure 7 As shown, the EDS spectra of carbon dots prepared in Example 1 and Comparative Example 1 of the present invention, where (A) is CDs, (B) is N-CDs, and (C) is N,P-CDs. Figure 7 It can be seen that the largest proportion of the entire carbon dot material is composed of C and O elements, and the corresponding doping elements can be identified on the surface of the material after doping modification.

[0076] like Figure 8 As shown, the infrared spectra of carbon dots prepared in Example 1 and Comparative Example 1 of the present invention, wherein (A) is CDs, (B) is N-CDs, and (C) is N,P-CDs. Figure 8 It can be seen that the three carbon dots with the same carbon source all contain hydroxyl (-OH), ketone bond (-CO-), carbonyl (-C=O), olefin (-C=C-), and ether bond (COC); after being modified by the passivating agent urea doping with N, the wavelength of the carbon dots is 3350cm -1 A secondary amide bond (-CONH-) and 2280 cm -1 The stretching vibration of R-CN near N and P co-doping at wave number 2405cm -1 With 740cm -1 The stretching vibrations of phosphorus-containing compounds (PH) and carbon-phosphorus bonds (PC) were identified nearby. The nitrogen-containing functional groups of the doping reagent urea exist in the form of wave number 3300 cm -1 There are double peaks nearby, and the carbon dot sample cannot identify the corresponding characteristic peaks. Therefore, the amino group in the doping reagent urea is connected to the carbon dot material, and the inorganic reagent potassium dihydrogen phosphate does not have a carbon-phosphorus bond, so the phosphorus element is also connected to the carbon dot material. At the same time, hydrothermal carbonization of lactose still retains a variety of effective functional groups under high temperature and high pressure conditions, and the bond force with curcumin is stronger, and the two have more contact sites.

[0077] like Fig. 9 As shown in Figure 1, the Raman spectra of carbon dots prepared in Example 1 and Comparative Example 1 of the present invention, where (A) is CDs, (B) is N-CDs, and (C) is N,P-CDs. Fig. 9 It can be seen that for fluorescent carbon dots, the larger the surface defects of the material itself, the stronger the gain effect on light intensity. The Raman spectrum is located at 1340cm -1 The peaks near the D band correspond to the sp 3 Defect, located at 1585cm -1 The peaks near belong to the G band, corresponding to ordered graphitic carbon sp 2 Clusters, indicating that the carbon dots have olefin groups. D / I G The area peak intensity ratio is 0.64. Compared with the comparative example 1 without any doping modification, the area ratio of D band to G band increases significantly, which indicates that the sp 3 The surface defects are greatly improved after being modified by N element doping, thereby strengthening the gain effect on light intensity and greatly improving the accuracy of detection.

[0078] like Fig.10 As shown in the figure, the light quantum yield measurement diagram of carbon dots prepared in Example 1 of the present invention and Comparative Example 1, wherein (A) is a blank solvent, (B) is N,P-CDs, (C) is N-CDs, (D) is CDs, and the fluorescent standard substance quinine sulfate is used as the reference substance. Fig.10(A) shows that the quantum yield of the fluorescent standard substance quinine sulfate measured under the same test conditions and operating methods is 54.59%, which is consistent with the actual standard value. Therefore, this test has a high reliability. Fig.10 (B), (C) and (D) show that the quantum yield of quinine sulfate measured with the fluorescent standard as reference is 129.67% of the carbon dot N, P-CDs prepared in Example 1, so the quantum yield of the fluorescent carbon dot N, P-CDs is 42.1%. Similarly, the quantum yields of N-CDs and CDs are 22.04% and 15.13% respectively. The quantum yield is an important indicator for measuring the energy conversion efficiency of fluorescent materials. The singleness of the raw materials usually has a very low quantum yield. The quantum yield can be increased by doping modification to improve the energy conversion efficiency of fluorescence excitation. Experiments show that N and P co-doping can effectively improve the quantum yield.

[0079] The fluorescence lifetime parameters of the carbon dots prepared with different lactose doping conditions were measured by steady-state / transient fluorescence spectrometer. The formula τ=(B1τ1 2 +B2τ2 2 ) / (B1τ1+B2τ2), where τ is the fluorescence lifetime, τ1 and τ2 are the time required for the fluorescence intensity to decay to 1 / e of the initial intensity, and B1 and B2 are the amplitudes of each exponent.

[0080] like Fig.11 As shown in the figure, the steady-state fluorescence lifetime results of carbon dots prepared in Example 1 of the present invention and Comparative Example 1. Fig.11 It can be seen from the measurement results that τ1 and τ2 are 4.33μs and 14.24μs respectively, B1 and B2 are 436.43nm and 217.14nm respectively, and the fluorescence lifetime of N,P-CDs is 10.48μs calculated by the above formula. The longer fluorescence lifetime of carbon dots means that the fluorescence signal can last longer. Especially as a detection probe, the longer fluorescence lifetime helps to provide a longer time window for imaging, thereby improving the signal-to-noise ratio and reducing background interference, further improving the detection accuracy.

[0081] The elemental composition of the carbon dots prepared with different lactose doping conditions was analyzed by X-ray photoelectron spectroscopy.

[0082] like Fig.12 As shown, the XPS peaks of each element of the carbon dots prepared in Example 1 and Comparative Example 1 of the present invention, where (A) is the O element, (B) is the N element, and (C) is the P element. Fig.12It can be seen that the fluorescent carbon doping elements after purification and impurity removal are successfully added to the carbon dot material with fluorescent properties. This preparation method is effective in doping and has a high effective doping atomic ratio. The successful incorporation of N elements in the form of NH bonds makes the surface of the carbon dots more passivated, creating more surface defects so that there are more active electrons in the excited state, and the number of energy level transitions after being excited is also greater, so that the light intensity has a qualitative leap; the successful incorporation of P elements in the form of PO / P=O bonds can not only make the prepared lactose-based carbon quantum dots have a smaller size and prevent carbon dots from agglomerating and settling, but also a large number of experiments have shown that co-doping with N elements can effectively promote the intersystem crossing (ISC) process and effectively fill triplet excitons, thereby extending the time for the luminescent electrons to absorb energy and transition to the excited state and then emit fluorescence in the form of radiation transition to return to the ground state, providing more response time for the spectral detection instrument, and at the same time significantly improving the optical properties of the fluorescent carbon dot material itself.

[0083] like Fig.13 As shown in the figure, the light intensity of carbon dots prepared in Example 1 of the present invention is plotted against pH stability, thermal stability and fluorescence decay rate, where (A) is acid-base stability, (B) is thermal stability, and (C) is fluorescence decay rate. Fig.13 It can be seen that the prepared carbon dots have excellent acid-base stability, that is, the solution system with different pH values ​​of 2 to 12 has little destructive power on light intensity. Even under pH conditions of 1 and 13, the light intensity retention rate is still above 50%. Since the fluorescent carbon dots with the best thermal stability have been screened out during the purification process, the influence of the thermal stability of the fluorescent carbon dots obtained by this preparation scheme on the light intensity fluctuates within 8%. The light intensity of the prepared fluorescent carbon dots will gradually weaken over time. The experiment will test the light intensity attenuation rate under different storage conditions for two weeks. Fig.13 As shown in (C), the attenuation rate under the storage conditions of refrigerated storage and light avoidance is about 6.01% per week, and the attenuation rate under natural light storage at room temperature is about 7.09% per week.

[0084] The invention adopts a theoretical system based on which the multicolor emission of fluorescent carbon dots is regulated by the size effect of the conjugated π domain of the fluorescent center, and utilizes the peak characteristics of the emission spectrum to quantitatively detect curcumin.

[0085] like Fig.14 As shown, the present invention uses fluorescence spectrum characteristics to quantitatively detect curcumin effect diagram, from Fig.14 It was found that with the increase of curcumin content, the half-peak width of the fluorescence emission spectrum of the coexisting solution of the two changed regularly, and the content of curcumin in the coexisting solution could be analyzed by analyzing the increment of the half-peak width.

[0086] The standard curve prepared by the detection method of the present invention is curcumin content-half peak width. The standard curve is used to take a sample containing curcumin and a carbon dot solution under the same conditions, and the curcumin content can be calculated by reading the half peak width data of the fluorescence spectra emitted by the two and substituting it into the standard curve equation.

[0087] like Fig.15 As shown, the content-half peak width standard curve of the carbon dots for quantitative detection of curcumin prepared in Example 1 of the present invention is Fig.15 It can be seen that the correlation coefficient R of the standard curve obtained by the method of the present invention is 2 =99.94%, and the half peak width increased by 2.1nm for each 20μL curcumin test solution added. The minimum detection limit of the method of the present invention was 1×10 -7 mol / L.

[0088] 2. Method of Comparative Example 2

[0089] The fluorescent carbon dots prepared by the same doping method using different carbon sources are all prepared by the material preparation and detection method of Example 1 to determine the curcumin content. The experimental results are shown in Table 1. It can be found that the light color purity of the fluorescent carbon dots prepared by the different carbon sources, that is, the initial half-peak width value, will also be different, but the peak wavelength of the fluorescence emission is near 450nm, that is, the fluorescent carbon dots prepared by the method of doping modification of the carbon dots prepared by the above-mentioned comparative example 2 are all carbon dot materials with blue as the main light color, and the surface state of the fluorescent carbon dots can be regulated by curcumin. Based on the principle that multicolor emission is regulated by the size effect, the effect of quantitative detection of curcumin can be achieved by observing the light color composition change, that is, the half-peak width change law. However, due to the reasons such as the light color purity of the material itself and the bonding fit with curcumin, the order of magnitude of the detection limit of different materials is not the same.

[0090] Table 1 Detection effect of carbon dots prepared from different carbon sources on curcumin

[0091]

[0092]

[0093] 3. Method of Comparative Example 3

[0094] Utilizing curcumin's own fluorescence, the fluorescence intensity is proportional to the concentration. By measuring the relationship between the fluorescence intensity and the corresponding concentration, a standard curve is made to measure the fluorescence intensity of the unknown sample and analyze the concentration. However, since curcumin is a weak fluorescent substance, the detection limit is high and the fluorescence intensity is greatly affected by interference factors such as salts, solubility and light intensity data floating. If accurate detection is achieved, strict pretreatment is required to overcome the error caused by the fluorescence intensity. Table 2 shows the interference of the substances that may affect its fluorescence properties in the composition of curcumin's natural substances to its measurement results. It can be found from Table 2 that salt substances that are easily soluble in water may affect the solubility of curcumin, but the solution is clear and the relative error is small, while slightly soluble or colored solutions will have a significant impact on the fluorescence intensity, so the relative error is large. For coexisting fluorescent substances, the light intensity interference is greater, so that the light intensity test data is distorted. Therefore, the method of comparative example 3 is used to detect curcumin and the influence of interfering substances must be strictly excluded.

[0095] like Fig.16 As shown, the standard curves of different curcumin determination methods of Comparative Examples 3 and 4 of the present invention are made, wherein (A) is the standard curve of the determination method of Comparative Example 3, and (B) is the relationship between lg(I0 / I)-curcumin concentration of Comparative Example 4. Fig.16 (A) is the standard curve made by the determination method of comparative example 3, and the fitting coefficient R 2 =99.68%. Due to the many interference factors of fluorescence intensity, it is necessary to repeat the test several times and take the average value to obtain a higher accuracy of the test result.

[0096] Table 2 Effect of interfering substances on detection effect in curcumin coexistence system

[0097]

[0098] 4. Method of Comparative Example 4

[0099] Fluorescence resonance energy transfer was achieved by using the overlapping absorption and emission spectra of curcumin and the fluorescent carbon dots prepared as the detection medium. Curcumin of different concentrations and the fluorescent carbon dots prepared in Example 1 were excited at an excitation wavelength of 350 nm, and the fluorescence intensity corresponding to the emission wavelength of 425 nm was recorded. The standard curve was as follows: Fig.16 (B) is the relationship between lg(I0 / I) and curcumin concentration, and the correlation fitting coefficient R 2 =99.61%. Since the observation index of the method in Comparative Example 4 is fluorescence intensity, the fluorescence intensity value fluctuates greatly due to many interference factors in repeated measurements in a short period of time, so the reliability of the test results is reduced. Since the fluorescence of curcumin is weak at low concentrations, the detection limit has been measured to be 1×10 -5Compared with the detection method of Example 1, the observation index is changed to the half-peak width of the fluorescence spectrum of the coexisting body, the stability of the detection index is greatly improved, and the corresponding detection result is more accurate. In addition, low concentration of curcumin can respond to the change of the half-peak width, and the test sensitivity is high.

[0100] The above embodiments describe the process of preparing the detection medium material of the present invention and the basic principles, main features and advantages of the method for quantitative analysis of fluorescent organic substances. Although the content of the present invention has been described in detail through the above preferred embodiments, it should be recognized that the above description should not be considered as a limitation of the present invention. After reading the above content, it will be obvious to those skilled in the art that various modifications and substitutions of the present invention will be made. Without departing from the scope of the principles of the present invention, the present invention will also realize quantitative analysis of homologous fluorescent organic substances by this principle and technical means, and such quantitative analysis detection methods all fall within the scope of protection of the present invention. Therefore, the scope of protection of the present invention should be limited by the attached claims.

Claims

1. A method for preparing doped carbon dots for quantitatively detecting curcumin based on the change of half-peak width of carbon dot fluorescence spectrum, characterized in that: The method includes: (1) adding a phosphate salt and an organic substance containing only nitrogen-doped elements to a carbon source, stirring the mixture to uniformly dissolve in water, and performing a hydrothermal reaction at 180° C. to 200° C. to obtain a fluorescent carbon dot solution; The carbon source is any one of glucose, starch, maltose, sucrose and lactose; (2) The obtained fluorescent carbon dot solution is filtered with an aqueous filter membrane, and the supernatant is obtained by centrifugation. The supernatant is dialyzed with a dialysis bag in pure water under magnetic stirring. The liquid inside the dialysis bag is aqueous doped blue fluorescent carbon dots, which is recorded as aqueous N,P-CDs solution; (3) The aqueous N,P-CDs solution was completely evaporated, anhydrous ethanol was added and fully dissolved again by ultrasound, and then filtered using an organic filter to obtain an alcohol-soluble N,P-CDs solution.

2. The preparation method according to claim 1, characterized in that: In step (1), the phosphate salt is potassium dihydrogen phosphate, and the organic matter containing only nitrogen-doped elements is urea; the molar ratio of the carbon source, the phosphate salt and the organic matter containing only nitrogen-doped elements is (2-4):10:

60.

3. The preparation method according to claim 1, characterized in that: In step (2), the pore size of the water filter membrane is 0.45 μm; the centrifugal speed is 10000 r / min and the time is 10 min.

4. The preparation method according to claim 1, characterized in that: In step (2), the molecular weight cutoff of the dialysis bag is 1000Da, the dialysis time is 16 to 48 hours, and the water is changed every 8 hours.

5. The preparation method according to claim 1, characterized in that: In step (3), the pore size of the organic filter head is 0.22 μm.

6. A doped carbon dot for quantitatively detecting curcumin based on the fluorescence spectrum characteristics of the carbon dots, obtained by the preparation method according to any one of claims 1 to 5.

7. The doped carbon dots according to claim 6, characterized in that: The doped carbon dots emit pure blue fluorescence at an excitation wavelength of 350 nm, with a light quantum yield of 41.86% and a fluorescence lifetime of 10.48 μs.

8. An application of the doped carbon dots as claimed in claim 6 in detecting the content of fluorescent organic matter, characterized in that: The app contains: The doped carbon dots as described in claim 6 are used as the detection medium, and photophysical regulation is used to change the half-peak width of the fluorescence spectrum to achieve quantitative analysis of the fluorescent organic matter to be tested.

9. The use according to claim 8, characterized in that: The application contains the following test results for curcumin content: The curcumin-regulated doped carbon dots as described in claim 6 have several bonding forces that cause the molecules to stack very closely, triggering a carbon dot size effect, resulting in a phenomenon of spectral polychromatic emission and thus affecting the spectral half-peak width. The curcumin content is analyzed by observing the spectral half-peak width.

10. The use according to claim 9, characterized in that: The app contains: The fluorescence spectrophotometer is set to an excitation wavelength of 350 nm and an excitation voltage of 700 V. The curcumin standard solution is added to the test solution containing the doped carbon dots as claimed in claim 6 and mixed thoroughly. The change in the half-peak width of the fluorescence emission spectrum is recorded, and a standard curve of the relationship between the curcumin content and the half-peak width is made. The curcumin content can be calculated by substituting the half-peak width of the spectrum of the synergistic effect of the test sample and the carbon dots into the linear equation.

Citation Information

Cited By

  • Portable fluorescent test paper for detecting sewage as well as preparation method and application of portable fluorescent test paper

    CN119959199A